2017
DOI: 10.1016/j.ijhydene.2017.04.081
|View full text |Cite
|
Sign up to set email alerts
|

AFM imaging and nanoindentation of polymer of intrinsic microporosity PIM-1

Abstract: Polymers of intrinsic microporosity (PIMs) have promising gas adsorption properties for potential applications such as incorporation into high-pressure hydrogen storage tanks in an effort to increase the storage capacity or decrease the operating pressure. Such applications require detailed mechanical characterisation and determination of the structureproperties relationships to enable optimisation of the interface between the polymer and the container. In this study, we show that Atomic Force Microscopy (AFM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Polak-Kraśna et al used AFM nanoindentation analysis to determine the elastic moduli of PIM-1 films at different indentation depths, 33 obtaining results that are in good agreement with data acquired with tensile tests and DMTA. 32 Song et al performed nanoindentation on PIM-1 to study the effect of thermal-oxidative treatment on the polymer stiffness.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Polak-Kraśna et al used AFM nanoindentation analysis to determine the elastic moduli of PIM-1 films at different indentation depths, 33 obtaining results that are in good agreement with data acquired with tensile tests and DMTA. 32 Song et al performed nanoindentation on PIM-1 to study the effect of thermal-oxidative treatment on the polymer stiffness.…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, a study of PIM aging, to seek greater understanding of the relationship between gas separation performance and mechanical properties on a time scale that is close enough to the normal lifetime of a membrane is desirable. The few reports on the mechanical properties of PIMs, using different techniques, reveal that the elastic modulus of PIMs are in the range that is typical of glassy polymers. , However, common tensile tests require multiple specimens of a relatively large sample size, and to the best of our knowledge a systematic analysis of the effect of physical aging on the mechanical properties of PIMs has never been performed. For situations where only a small amount of sample is available, a versatile and widely used alternative is force spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…They have been extensively studied, [17] and used to create separation membranes [18][19][20][21][22][23][24][25][26][27][28] and gas storage materials. [12,19,29,30] Our group recently studied the capacity of PIM-1 for hydrogen storage and its mechanical properties, [31,32] and demonstrated that its relatively limited surface area and hydrogen uptake capacity can be significantly enhanced by addition of high-surface area fillers. [33] An important parameter to consider when evaluating these materials is their long-term behaviour and stability.…”
Section: Introductionmentioning
confidence: 99%
“…3 (c)). The different mechanical properties at various depths were related to the stiffer outer layer and more elastic inner chains of the polymer during the evaporation of the solution [57] . The retract curve exhibited only one consecutive line and almost returned back to the initial position of the approach curve, suggesting an elastic and reversible deformation of the membrane.…”
Section: Resultsmentioning
confidence: 99%